Analisis Analysis The Ability of Students Mathematical Literacy on The Realistic Mathematic Education Learning with The Loads of The Character of Islam - Karyadi, Karyadi; Suyitno, Hardi; Karomah Dwidayati, Nur (Universitas Negeri Semarang, 2018)
The ability of students mathematical literacy (KLM) in MTs is still low because problems related to daily life are not used as the source of concept formation. The purpose of this study was to find out whether the Realistic Mathematic Education (RME) learning with character of Islam effectively improves students KLM and analyzed. Type of research used mixed methods with concurrent embedded research design with two types of data. Quantitative data are the value KLM in pretest and posttest which is analysed by ttest, gaintest and qualitative through three procedures namely reduction, presentation and conclusion. The two classroom research subjects are experiment and expository. The result of this research experiment is effective, because (1) experiment KLM has reached classical completeness exceeding 75%; (2) improvement of student KLM on experiment higher than student expository. The ability of students mathematical literacy on the category is very good, good and good enough.